2023
DOI: 10.2147/prbm.s404063
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Active Social Media Use on General Trait and Online-Specific State-FoMO: Moderating Effects of Passive Social Media Use

Abstract: Given the prevalence of the fear of missing out (FoMO) phenomenon and the limitations regarding understanding the relationship between social media use and FoMO, this research examines the links that bind different types of social media usage to different aspects of FoMO. Methods: In the scope of this research, a structural equation modeling was developed to investigate the intricate connections that exist between active social media use (ASMU), passive social media use (PSMU), online-specific state-FoMO, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
(148 reference statements)
0
1
0
Order By: Relevance
“…Specifically, exploring associations with other indicators of social media use and personality traits might be valuable in future research. This could include examining passive/active social media use, social comparison orientation, maximizing tendency, and regret tendency (e.g., S.-C. Lin & Jian, 2022;Mao & Zhang, 2023). Moreover, it would be worthwhile to investigate its associations with psychological well-being indicators, such as stress and anxiety (e.g., Elhai et al, 2021a).…”
Section: Limitationsmentioning
confidence: 99%
“…Specifically, exploring associations with other indicators of social media use and personality traits might be valuable in future research. This could include examining passive/active social media use, social comparison orientation, maximizing tendency, and regret tendency (e.g., S.-C. Lin & Jian, 2022;Mao & Zhang, 2023). Moreover, it would be worthwhile to investigate its associations with psychological well-being indicators, such as stress and anxiety (e.g., Elhai et al, 2021a).…”
Section: Limitationsmentioning
confidence: 99%
“…Most of these investigations focused on the consequences of FoMO on different well-being variables by also considering individuals' social media engagement [13,14]. In this context, a meta-analysis focusing on private FoMO found that social media engagement can be both an antecedent and consequence of experiencing FoMO [15][16][17][18][19]. However, media usage is not limited to people's private spheres but also becomes crucial in the context of many working environments [20].…”
Section: Theoretical Backgroundmentioning
confidence: 99%